2021
DOI: 10.29393/chjaas37-25saja80025
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Extensive Cattle and Sheep Production Systems in Southern Chile

Abstract: Extensive livestock systems have decreased in the last decades. In general, these systems are characterized by low profitability, but they have a key role on environment conservation, maintenance of rural population, and health of meat and milk consumers. The present study was carried out in 2017 with 29 livestock farmers in the cold steppe area, Rio Ibáñez District (Comuna de Rio Ibánez), Aysén Region, Chile. The objective of this work was to compare the characteristics of extensive cattle and sheep farms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Their natural evolution in particular regions/conditions has granted them advantages over conventional breeds such as Angus, as they can consume low-quality diets with higher efficiency, leading to the production of a protein with decreased environmental impacts on soil and vegetation [8][9][10]. However, meat produced from local breeds does not always satisfy the requirements of the meat industry, and hence, this meat is commercialized through niche markets [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Their natural evolution in particular regions/conditions has granted them advantages over conventional breeds such as Angus, as they can consume low-quality diets with higher efficiency, leading to the production of a protein with decreased environmental impacts on soil and vegetation [8][9][10]. However, meat produced from local breeds does not always satisfy the requirements of the meat industry, and hence, this meat is commercialized through niche markets [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of government and education institutions are also immensely needed. Avilez et al, (2021) reported that a collaboration between farmers and government institutions on intensive rearing system is necessary for improving livestock profitability. Pereira et al, (2020) added that supports for farmers on access to finance, improvement of guidance services, land regulation, and infrastructure improvement are also required.…”
Section: Total Economic Value Of Cattle Resourcesmentioning
confidence: 99%